Characterization of protein-protein interactions involving G-Protein-Coupled Receptor 143 by computational and pharmacological methods - Büschbell, Beatriz Theresa Ruth (2024)
Tese de Doutoramento em Biologia Experimental e Biomedicina apresentada ao Instituto de Investigação Interdisciplinar